2023
DOI: 10.1002/macp.202300063
|View full text |Cite
|
Sign up to set email alerts
|

Polyether Synthesis through Reductive Etherification Reaction Strategy

Abstract: The reductive etherification reaction (RER) of carbonyl groups (aldehydes or ketones) through silane as a reducing agent together with Bronsted or Lewis acid affords the synthesis of symmetrical and unsymmetrical ethers. This strategy is applied at the macromolecular level for the first time in 1993, and isophthalaldehyde is self‐polymerized in the presence of triethylsilane (Et3SiH)/ tritylperchlorate (TrClO4) to yield polyethers with low to moderate molecular weights. Next, the polyethers with alternating st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 74 publications
(146 reference statements)
0
1
0
Order By: Relevance
“…[51][52][53][54][55][56][57] After the pioneering studies of Doyle on the RER, this strategy has been successfully employed at the macromolecular level by successive studies of the Yokozawa group [58][59][60][61][62] and the recently published studies by our group. [63][64][65][66][67] Notably, our studies have shown that chlorodimethylsilane (CDMS), which has both reducing agent and Lewis acid characteristics, introduced by Lee and Morandi, 68 is an effective silane compound for obtaining polyethers as well as alkoxy pendant polymers. 63,64 More recently, we showed that when a polymer possessing pendant aldehyde units was subjected to a CDMSmediated RER using thiols, thioacetal and thioether structures were obtained in the side chain of the polymer.…”
Section: Introductionmentioning
confidence: 99%
“…[51][52][53][54][55][56][57] After the pioneering studies of Doyle on the RER, this strategy has been successfully employed at the macromolecular level by successive studies of the Yokozawa group [58][59][60][61][62] and the recently published studies by our group. [63][64][65][66][67] Notably, our studies have shown that chlorodimethylsilane (CDMS), which has both reducing agent and Lewis acid characteristics, introduced by Lee and Morandi, 68 is an effective silane compound for obtaining polyethers as well as alkoxy pendant polymers. 63,64 More recently, we showed that when a polymer possessing pendant aldehyde units was subjected to a CDMSmediated RER using thiols, thioacetal and thioether structures were obtained in the side chain of the polymer.…”
Section: Introductionmentioning
confidence: 99%